2011
DOI: 10.1038/ncomms1282
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cell-surface prion protein conversion revealed using a novel cell system

Abstract: Prion diseases are fatal neurodegenerative disorders with unique transmissible properties. The infectious and pathological agent is thought to be a misfolded conformer of the prion protein. Little is known about the initial events in prion infection because the infecting prion source has been immunologically indistinguishable from normal cellular prion protein (PrPC). Here we develop a unique cell system in which epitope-tagged PrPC is expressed in a PrP knockdown (KD) neuroblastoma cell line. The tagged PrPC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
155
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(170 citation statements)
references
References 53 publications
8
155
0
Order By: Relevance
“…We recently reported that after the inoculation of prions, newly generated PrP Sc appeared on the cell surface, early endosomes, and late endosomes of N2a cells (Yamasaki et al, 2014a). These cell biological studies suggest the intracellular vesicular compartments to be the major sites for PrP Sc formation, whereas it was reported that PrP Sc formation occurs on the cell surface within a minute (Goold et al, 2011). On the other hand, ultrastructural studies using the brains of prion-infected mice showed that PrP Sc was frequently detected on the plasma membranes of neuropils, and occasionally in the intracellular vesicles (Godsave et al, 2008(Godsave et al, , 2013Jeffrey et al, 1992Jeffrey et al, , 1994.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…We recently reported that after the inoculation of prions, newly generated PrP Sc appeared on the cell surface, early endosomes, and late endosomes of N2a cells (Yamasaki et al, 2014a). These cell biological studies suggest the intracellular vesicular compartments to be the major sites for PrP Sc formation, whereas it was reported that PrP Sc formation occurs on the cell surface within a minute (Goold et al, 2011). On the other hand, ultrastructural studies using the brains of prion-infected mice showed that PrP Sc was frequently detected on the plasma membranes of neuropils, and occasionally in the intracellular vesicles (Godsave et al, 2008(Godsave et al, , 2013Jeffrey et al, 1992Jeffrey et al, , 1994.…”
Section: Introductionmentioning
confidence: 90%
“…Although PrP Sc has been reported as detected on the cell surface of prion-infected immortalized neuronal cells (Goold et al, 2011;Rouvinski et al, 2014;Yamasaki et al, 2012), cell biological studies using immortalized cell lines strongly suggested that the PrP Sc formation takes place at cellular compartments along with the endocytic recycling pathway such as the endocytic recycling compartments, or those along with the endo-lysosomal pathway such as multivesicular bodies (Beranger et al, 2002;Borchelt et al, 1992;Marijanovic et al, 2009;Pimpinelli et al, 2005;Veith et al, 2009;Yamasaki et al, 2012Yamasaki et al, , 2014a. In contrast, ultrastructural analyses using brains of prion-infected mice and hamsters identified PrP Sc frequently at the plasma membranes and less frequently at synapses and compartments of the endolysosomal system (Arnold et al, 1995;Fournier et al, 2000;Godsave et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of PrP C to PrP Sc in cells following prion infection is rapid, resulting in synthesis of PrP Sc at the cell plasma membrane. 4 However, the means by which misfolded PrP traffics around the cell and its sub-cellular interactions remain ill-defined. Nevertheless, the PrP conversion process is associated with various alterations in cellular function, including signaling, metabolism, gene expression, and protein sorting and degradation.…”
Section: Misfolded Prp and A Novel Mechanism Of Proteasome Inhibitionmentioning
confidence: 99%
“…MAVS fiber formation in cells has not been observed, and may provide insight into the mechanism by which the prion-like conformation of MAVS differs from the inactive conformation, and how nucleation at the mitochondrial membrane occurs. Notably, a recent study demonstrated that the plasma membrane is the initial site of conversion of cellular PrP to the prion form [12], raising the possibility that MAVS conversion to the activated prion-like form also requires membrane association, in this case with mitochondria. Questions also remain regarding the role of MAVS-RIG-I interaction in the MAVS activation/aggregation process.…”
mentioning
confidence: 99%